P176 Indications and demographics of domiciliary NIV set-ups in an acute hospital. (14th November 2013) - Lynch, CA; O'Sullivan, O; Bwika, J; Santana-Vaz, N; Oakes, A; Beauchamp, B; Mukherjee, R
Abstract : Background: Domiciliary NIV is being increasingly used to treat chronic ventilatory failure but there is little site-level data available describing the demographics of patients on domiciliary NIV under centres which have developed over the last decade. At our central England teaching hospital, domiciliary NIV is either set up following an acute admission with hypercapnic acidotic respiratory failure through the dedicated 11-bedded ward-based unit or electively, through the surveillance of patients at risk of ventilatory failure. Currently we have 262 patients on domiciliary NIV. We aimed to analyse the primary diagnosis and demographics of patients started on domiciliary NIV in the last 18 months. Method: A retrospective analysis of all patients started on domiciliary NIV at a 1000-bedded central England teaching hospital from 01 Jan 2012 to 30 June 2013. Results: A total of 90 patients were analysed and there was a slight male predominance (55.5%). The mean age at initiation of domiciliary NIV was 56.3 years (SD 18.9, median 52.5 years). Primary diagnoses (reason for domiciliary NIV) were 1.neuromuscular disorders (35.5%); 2. obesity-related disorders (33.3%); 3. COPD (13.3%); 4. thoracic cage disease other than obesity (15.6%) and 5. central pathology (2.3%). Of the COPD patients, 7/12 (58.33%) were GOLD class 4, 4/12 (33.33%) were GOLD class 3 and 1/12 (8.33%) were GOLD class 2. The mean domiciliary NIV set-up per month was 4.68 (SD 3.16). There was no clear relationship between number of set-ups per month and corresponding calendar month; 22.2% patients (20/90) had long term oxygen therapy prescribed with their NIV. Discussion: The role of domiciliary NIV is expanding with greater numbers of people living with chronic ventilatory failure, and this is set to increase with the rising problem of (a) obesity-related respiratory disorders and (b) improved survival of children with neuromuscular weakness. This study highlights the need for a domiciliary NIV registry for improved resource and workforce planning.